2022
DOI: 10.1364/oe.449382
|View full text |Cite
|
Sign up to set email alerts
|

Determination of detonation characteristics by laser-induced plasma spectra and micro-explosion dynamics

Abstract: Determination of macroscale detonation parameters of energetic materials (EMs) in a safe and rapid way is highly desirable. However, traditional experimental methods suffer from tedious operation, safety hazards and high cost. Herein, we present a micro-scale approach for high-precision diagnosis of explosion parameters based on radiation spectra and dynamic analysis during the interaction between laser and EMs. The intrinsic natures of micro-explosion dynamics covering nanosecond to millisecond and chemical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The plume of all samples is closer to that of the lower energy materials (images of the plume of lower energy materials can be found in the literature) 40,41 which consume more energy in luminescent radiation unrelated to the explosion, resulting in brighter radiation and lower explosive performance.…”
Section: Explosive and Propellant Performance Predictionmentioning
confidence: 67%
“…The plume of all samples is closer to that of the lower energy materials (images of the plume of lower energy materials can be found in the literature) 40,41 which consume more energy in luminescent radiation unrelated to the explosion, resulting in brighter radiation and lower explosive performance.…”
Section: Explosive and Propellant Performance Predictionmentioning
confidence: 67%
“…Yoh et al investigated laser-induced shock waves stimulated by pulse energy above 1 J on the time scale of nanoseconds, and found that the shock waves had a similar structure to actual macroscopic detonation waves. 14 Our previous study established a close correlation between laser-induced micro-detonation and macroscopic detonation based on the laser-induced plasma spectra and dynamics covering nanoseconds to milliseconds, and successfully predicted four sensitivities of certain singlecompound explosives accurately by acquiring laser-induced plasma spectra with an integral time of 30 ms. 15,16 The above results veried that there is substantial timedependent detonation information hidden in the early plasma cooling stage under high-uence laser irradiation. The critical physical processes for laser-induced detonation are not completely understood.…”
Section: Introductionmentioning
confidence: 70%
“…14 Our previous study established a close correlation between laser-induced micro-detonation and macroscopic detonation based on the laser-induced plasma spectra and dynamics covering nanoseconds to milliseconds, and successfully predicted four sensitivities of certain single-compound explosives accurately by acquiring laser-induced plasma spectra with an integral time of 30 μs. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Reactive plasmas generated by pulsed laser ablation resemble the explosive expansion dynamics and fireball combustion chemistry of macroscopic detonations at the laboratory scale. [1][2][3] Temperatures and timescales associated with the combustion chemistry of nanosecond laser ablation (LA) plasmas and aluminized high explosives have been shown to be very comparable. 3 Furthermore, LA plasmas have also been used as physicochemical surrogates for nuclear fireballs to develop reaction mechanisms and condensation pathways for nuclear fallout particle formation and debris distributions.…”
Section: Introductionmentioning
confidence: 99%